The Effectiveness of Baby Massage in Increasing Infant's Body Weight - Sirait, Lusiana Lusia; Simatupang, Gusti Seventina (poltekkes kemenkes mataram, 2024)
Increasing body weight is an indicator for assessing baby growth. The baby's weight gain in the first year of life is based on whether the baby receives good nutrition from birth to the first six months. The weight gain per week ranges from 140-200 grams. Children 1-12 months experience rapid growth, so it is necessary to maintain the baby's weight according to age. They obtain optimal growth and development results from the interaction of several interrelated factors: genetic factors, nutrition, socio-economic status, health status, hormonal factors, environmental factors, cultural environment, parenting patterns, physical activity, and stimulation. Dietary factors play an essential role in the growth process because they influence the nutritional status of children. Stimulation factors are also critical to stimulate children's growth. Massage is a technique that combines the physical benefits of human touch with emotional benefits such as bonding and weight gain. This research aims to determine the relationship between baby massage and weight gain in babies at the Kasih Bunda Clinic in 2023. This type of research is the Shapiro-Wilk Test with a non-equivalent control group design and a pretest-posttest design. Then, measurements were taken before the pretest on both groups of respondents; then, measurements were carried out again (Posttest) to determine the difference in pretest and posttest body weight. The type of sampling uses purposive sampling. The results of the research were carried out with a confidence level of 95% (α=0.05), as proven by the p-value: 0.000 (p-value ≤ 0.05). In conclusion, a relationship exists between giving baby massages and increasing baby weight at the Kasih Bunda Clinic in 2023. It is hoped that health workers will make baby massage one of the counseling materials for mothers to support the increase in baby weight and teach them how to do proper baby massage.